FACTORS OF DEVIATION CAUSES IN TAFSIR (Causes of Errors and Deviations in Interpretation: Tafsir bi al-Ma'tsur, Tafsir bi al-Ra'yi, and Tafsir bi al-Isyarah) - Abdullah, Zainuddin (Institut PTIQ Jakarta, 2020)
This paper discusses the factors that cause irregularities in interpretation, namely focusing on the factors causing errors and irregularities in interpretation: interpretation bi al-ma'tsur, interpretation bi al-ra'yi, and interpretation bi al-isyarah. This paper shows that the deviation in interpretation is caused by several factors, namely: 1) Deviation due to the Isra'iliyyat factor; 2) Deviations due to the nahwu school of thought; 3) Deviations due to factors not knowing Arabic rules; 4) Deviations due to the bias factor of the school as happened in the commentary of the Mu'tazilah; 5) Deviations due to the bias factor of the school as happened in the Shi'ah interpretation book; 6) Deviations due to the bias factor of the school as happened in the commentaries of the Khawarij; 7) Deviations due to the bias factor of the school as happened in the commentaries of the Sufis; 8) Deviations in the book of scientific interpretation, which states that the Koran includes all kawniyyah knowledge both globally and in detail; 9) Deviations due to contemporary demands. Furthermore, this study offers three theories of truth testing to answer the phenomenon of interpretive deviation, including: a) Coherence theory: a test of consistency b) Correspondent theory: a test of equality with facts c) Pragmatic theory: a test of expediency. A theory that can be used to minimize deviations in the interpretation of the Qur'an.